دور ديوان الرقابة المالية في كشف مخالفات العقود الحكومية - معتز علي صبار (PROSPECTIVE RESEARCHES, 2023)
Due to the modern state’s expansion of its activity and its interference in various aspects of life، this development in the role of the state and the expansion of its activity necessitated the creation of specialized supervisory bodies that follow up the activities and work of state institutions and departments. Professionally specialized and exercises control over the activities practiced by the various state facilities and institutions, whether they are linked to a ministry or not, or that enjoy financial and administrative independence، and even semi-governmental institutions are subject to the control of the Bureau as well. The Office of Financial Supervision is characterized as an institution that is described as enjoying independence and impartiality as it is an independent authority from the government in the exercise of its supervisory activity. Government contracts are one of the most important means through which the government can accomplish the tasks entrusted to it in order to provide public services and to complete service and vital projects, and the implementation of these contracts entails spending cash from public money. However, these spending operations may be marred by a waste of public money or the commission of corruption, and here comes the role of the Financial Supervision Bureau in auditing these contracts concluded by state institutions and departments, and ensuring the extent of their safety and compatibility with the instructions for implementing government contracts, in terms of the authority of the party that undertakes their conclusion and the necessary allocations To implement them, however, the reality of practical application, which we discern from the nature of the reports prepared by the Federal Financial Supervision Bureau، in addition to the nature of the measures taken in light of them, indicates the weakness or lack of the powers of the Bureau and its decisions in terms of binding and deterring violators, so we will focus in our research on the role it plays The Bureau in its monitoring of government contracts, and diagnosing weaknesses in its work, to demonstrate the effectiveness and efficiency of this role in detecting and combating financial and administrative corruption that is committed when executing government contracts.